1982
DOI: 10.1002/dev.420150307
|View full text |Cite
|
Sign up to set email alerts
|

Control of sleep‐wake states in the infant rat by features of the mother‐infant relationship

Abstract: A series of experiments in 2 strains of Wistar rats explored which aspects of maternal separation were responsible for the sleep disturbance of the young. Neither their own mother, after mammary duct ligation, nor constant intragastric infusion of nutrient during the day of separation were found to ameliorate significantly the changes in sleep-wake state organization. However, a periodic nutrient delivery schedule and a formula closely resembling rat milk each ameliorated, and together entirely prevented, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(38 citation statements)
references
References 20 publications
0
38
0
Order By: Relevance
“…The significant correlation between active sleep and maternal milk yield/energetic investment in the infant is consistent with the attachment hypothesis. Hofer (1987aHofer ( , 1987bHofer and Shair 1982) and his colleagues have shown that nursing (the paradigmatic attachment behavior) in the rat is controlled by an elaborate set of cues all embedded in sleep. Infants sleep while they are nursing and suck while they are asleep.…”
Section: Sleep Quotas and Nursing Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant correlation between active sleep and maternal milk yield/energetic investment in the infant is consistent with the attachment hypothesis. Hofer (1987aHofer ( , 1987bHofer and Shair 1982) and his colleagues have shown that nursing (the paradigmatic attachment behavior) in the rat is controlled by an elaborate set of cues all embedded in sleep. Infants sleep while they are nursing and suck while they are asleep.…”
Section: Sleep Quotas and Nursing Variablesmentioning
confidence: 99%
“…REM inhibition after maternal separation, on the other hand, persists (although in a slightly attenuated form) into the despair phase of the "protest"-then-"despair" separation sequence (Hofer 1987a(Hofer , 1987bHofer and Shair 1982).…”
Section: Notesmentioning
confidence: 99%
“…It has a direct impact on genetically inherited risk factors and resilience. [11][12][13][14][15][16][17][18][19][20][21][22][23] With the aim of measuring the contribution of parental behavior to the development of appropriate bonds between parents and children, the Parental Bonding Instrument (PBI) was created in 1979 through successive factor analyses, based on 114 items taken from the literature deemed as major parental qualities for normal development. 24 PBI is a self-administered Likert scale (0 to 3) instrument, with 25 questions related to father and mother, in which subjects answer how similar those behaviors were to their parents' behavior until the age of 16 years.…”
Section: Introductionmentioning
confidence: 99%
“…Specific behaviors of the dam regulate the functioning of many specific behavioral and physiological systems in pups. For instance, periodic milk delivery modulates the sleep-wake cycle of pups (Hofer & Shair, 1982), tactile stimulation, similar to that used in the present study, maintains normal ornithine decarboxylase levels (Butler et al, 1968;Evoniuk et al, 1979;Kuhn et al, 1978), and some unknown nonnutritive aspect of contact with the dam maintains adrenocortical activity at normal levels (Smotherman, 1983;Stanton & Levine, 1984). The results of the present paper indicate that some nonspecific aspect of maternal physical stimulation may also serve to-regulate the body and brain temperature of neonatal pups.…”
Section: Discussionmentioning
confidence: 61%